Effect of CuO and TiO2 on the sintering temperature and dielectric properties of BaWO4 for LTCC applications. Issue 17 (1st December 2020) - Dong, Ye; Zhu, Haikui; Gu, Huidong; Bian, Wenjie; Ta, Shiwo; Zhang, Qitu
Abstract: A series of (1- x ) BaWO4 - x CuO low-temperature sintered composite ceramics were prepared via co-firing the mixture of BaWO4 and CuO in the first part of this study. The sintering temperature of BaWO4 was decreased from 1150 °C to 950 °C when a little amount of CuO was used as sintering aids. The 0.95BaWO4 -0.05CuO sample heated at 950 °C for 4 h had good dielectric performance ( Q  ×  f  ~ 31, 847 GHz, ε r  ~ 7.99, τ f  ~ −81.7 ppm/°C). However, the negative τ f was too large to apply to practice. To solve this problem, the rutile phase TiO2 nano-particle with a large positive temperature coefficient of +450 ppm/°C was added as τ f compensator in the second part of the study. TiO2 powders not merely improved the temperature stability, but promoted the grain growth. However, the ε r value increased from 10.5 to 12.6 and Q×f value decreased slightly as TiO2 content increased from 0.30 to 0.45. The 0.65 (0.95BaWO4 -0.05CuO) −0.35TiO2 composite ceramic displayed an optimum performance ( Q  ×  f  ~ 22, 012 GHz, ε r  ~ 11.21, τ f  ~ −2.9 ppm/°C). Such a sample was chemically compatible with silver, implying that it can be implemented on LTCC applications.